Premenopausal Women With a Diagnosis of Endometriosis Have a Significantly Higher Prevalence of a Diagnosis or Symptoms Suggestive of Restless Leg Syndrome: A Prospective Cross-Sectional Questionnaire Study - Tempest, Nicola; Boyers, Madeleine; Carter, Alice; Lane, Steven; Hapangama, Dharani K. (Frontiers in Endocrinology, 2021)
Abstract Background Endometriosis and restless leg syndrome (RLS) are both chronic conditions that can negatively affect a woman’s quality of life. A higher prevalence of RLS is seen in women and particularly in those who are pregnant, suggesting a possible ovarian hormonal influence. Endometriosis is a common (affecting 1 in 10 women) oestrogen driven gynaecological condition, and the prevalence of RLS in women with symptoms or a diagnosis of endometriosis is unknown. Methods A prospective, cross-sectional, observational self-completed questionnaire study was distributed to 650 pre-menopausal women attending the gynaecological department at Liverpool Women`s Hospital over a period of 4 months. 584 questionnaires were returned and 465 completed questionnaires were included in the final dataset. Data on RLS-associated (The International Restless Leg Syndrome Study Group rating scale) and endometriosis-associated (modified-British Society of Gynaecological Endoscopists pelvic pain questionnaire) symptoms were collected. Results Women who reported a prior surgical diagnosis of endometriosis had a greater risk of having a prior formal diagnosis of RLS (OR 4.82, 95% CI 1.66,14.02) and suffering RLS symptoms (OR 2.13, 95% CI 1.34-3.39) compared with those without a diagnosis. When women with either a formal surgical diagnosis or symptoms associated with endometriosis group together, they also have a significantly increased risk of having either a formal diagnosis or symptoms suggestive of RLS (OR 2.49, 95% CI 1.30, 3.64). In women suffering with endometriosis-associated symptoms, the cumulative endometriosis-associated symptom scores demonstrated a modest positive correlation with RLS severity scores (r=0.42 95% CI 0.25 to 0.57). Conclusions This is the first study highlighting an association between the symptoms relevant to the two chronic conditions RLS and endometriosis, showing that women with a reported prior surgical diagnosis or symptoms suggestive of endometriosis have a significantly higher prevalence of a prior formal diagnosis or symptoms suggestive of RLS. This data will help in facilitating the discovery of novel therapeutic targets relevant to both conditions. The simultaneous treatment of these conditions could potentially lead to improvement in the overall quality of life for these women.